Functional Involvement of ADRA1D in Cutaneous Melanoma Progression and Angiogenesis: Functional of ADRA1D in Cutaneous Melanoma Progression - Wang, Jianqiao; Ning, Danmei; Xie, Dong; Chen, Xiaoxiao; Cao, Xianwei; Wan, Chuan (Cellular and Molecular Biology, 2023)
Cutaneous melanoma is a highly aggressive and malignant skin cancer, and its high recurrence rate and drug resistance increase the difficulty of treating advanced-stage patients. Studies have revealed that treatment via stimulation of alpha-1 adrenergic receptor (ADRA1) subtypes inhibits melanoma growth in mice. However, the associations between alpha-1D adrenergic receptor (ADRA1D) and cutaneous melanoma are poorly understood. Tissue specimens from 16 pairs of patients with a pigmented nevus and cutaneous melanoma were analyzed for ADRA1D expression using immunohistochemical staining. Western blotting and RT-qPCR were carried out in order to detect ADRA1D expression levels in melanoma cells and human epidermal melanocytes (HEMs), hypoxia-inducible factor-1α (HIF-1α), and vascular endothelial growth factor (VEGF) levels in HUVECS. A375 cells were transfected with a lentivirus overexpressing ADRA1D. Wound-healing, Transwell, and cell proliferation assays were utilized to identify the ADRA1D effect on the migration, invasion, and proliferation of the two groups of A375 cells in vitro. In order to evaluate the function of ADRA1D in vivo, a melanoma xenograft model was developed in immunodeficient mice. ADRA1D was low expressed in cutaneous melanoma tissues. Overexpression of ADRA1D inhibited the tubulation and migration of HUVECs in vitro. Overexpression of ADRA1D significantly decreased the HIF-1α and VEGF expression. Overexpression of ADRA1D inhibited the invasion and proliferation of A375 melanoma cells in vitro and reduced its angiogenesis in vivo. ADRA1D inhibits cutaneous melanoma growth and angiogenesis. It attenuates melanoma cell proliferation and invasion. Meanwhile, its anti-angiogenic effect is achieved by negatively regulating the HIF-1α/VEGF axis in melanoma tissue, thereby attenuating the growth of cutaneous melanoma and reducing the potential of metastasis.